2010
DOI: 10.1108/10569211011025961
|View full text |Cite
|
Sign up to set email alerts
|

Personality traits and work performance in a duty‐free industry

Abstract: PurposeThe purpose of this paper is to examine the role of personality traits in affecting employees' work performance.Design/methodology/approachUsing a self‐administered questionnaire, 582 employees from a duty‐free organization are surveyed in order to examine the hypotheses of the study.FindingsSome personality traits are found to be significant in predicting employees' work performance. Some demographic factors such as gender are found to be mediating the links between traits and performance.Practical imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The "Five-Factor Model" has been commonly used with studies of personality traits. Some personality traits are found to be significant in predicting employees' work Performance (Suliman et al, 2010). Hogan et al (1994) concluded that personality affect leadership behavior.…”
Section: Personality Traitsmentioning
confidence: 99%
“…The "Five-Factor Model" has been commonly used with studies of personality traits. Some personality traits are found to be significant in predicting employees' work Performance (Suliman et al, 2010). Hogan et al (1994) concluded that personality affect leadership behavior.…”
Section: Personality Traitsmentioning
confidence: 99%
“…[3], [4], [5], and [6] have conducted researches and concluded that personality influences performance. In contrast, [7], [8], [9], and [10] have shown the different results, and thus, presented different statement.…”
Section: Introduction Backgroundmentioning
confidence: 92%
“…The results of research by experts found that personality dimensions can be related to performance, and can be used as a tool to predict success in work [9][10]. It should be understood that individual factors and environmental factors form the behavior of employees and their effects on performance achievement [11][12].…”
mentioning
confidence: 99%